Effect of Oral Immunotherapy on Nasal Blockage in Experimental Allergic Rhinitis - Takeshi Nabe; Kayoko Kubota; Tetsuya Terada; Hiroshi Takenaka; Shigekatsu Kohno (Elsevier, 2005)
We previously reported that when Japanese cedar pollen was prophylactically p.o. administered before a sensitization stage in a guinea-pig model of allergic rhinitis, pollen-induced nasal blockage was suppressed. In this study, we evaluated whether the oral immunotherapy is also effective when the pollen extract was administered starting from the day when the nasal blockage was clearly induced and whether the effectiveness continued after cessation of the immunotherapy. Sensitized animals were repeatedly challenged by pollen inhalation once every week. After the 7th challenge, the extract was orally administered twice a week until the 30th challenge. At the 11th challenge, the oral immunotherapy showed inhibition of the biphasic nasal blockage. The effectiveness was consistently observed during the immunotherapy until the 30th challenge. Furthermore, the increased nasal responsiveness to intranasal application of leukotriene D4 was markedly suppressed by the immunotherapy. Interestingly, even after cessation of the therapy, inhibition of the nasal blockage was sustained for more than 2 months. Nevertheless, neither sneezing nor antigen-specific IgE antibody production was substantially influenced by the immunotherapy. In conclusion, Oral immunotherapy may be clinically useful for allergic nasal blockage. Mechanisms underlying the effectiveness may be associated with the hyporesponsiveness of the nasal mucosa to released mediators. Keywords:: allergic rhinitis, animal model, oral immunotherapy, nasal blockage, pollenosis